Family in the picture, 1958 - 2013 - Friedlander, Lee 1934- (Yale University Art Gallery, 2013)
Designed and conceived to complement 'In the Picture', his 2011 volume of self-portraits, Lee Friedlander's 'Family in the Picture' is the family album of one of the most restless and inventive figures in the history of photography. The sequence of over 350 pictures begins with images of Friedlander's wife, Maria, at the beginning of their marriage, and interweaves major life events such as births, weddings and funerals with moments that are less outwardly momentous yet equally moving. Although some of the pictures are well known, the majority of images have only recently been unearthed from Friedlander's personal archive. This compendium of pictures, spanning over a half-century, chronicles the photographer's family with arresting frankness, poignancy, and a moral: that life goes on